Kajian Permasalahan Getaran pada Pelat dan Balok Beton Bertulang di Gedung E Fakultas Teknik Universitas Lampung - Firdasa, Silsila Jana; Alami, Fikri; Helmi, Masdar (Universitas Lampung, 2020)
The planning of a building has some criterias that need detailed attention which are the stiffness, strength, stability, flexibility and economical aspect. This result focus for building planner which is need the experimental method that use tools such as hammer test, Ultrasonic Pulse Velocity (UPV) and accelerator. Hence, the numerical method used SAP 2000 v.14.14.0.0. This result the frequency of the building was 1,953 Hz and the acceleration was 0,263 m/s2. Based on the SAP 2000 v.14.14.0.0 calculation, the building frequency was 7,078142 Hz and the acceleration was 0,001005 m/s2. The different results between those two methods were caused by unsatisfying building quality that caused the difference of result between those two methods. The building frequency fitted the specification attached on ISO 2631-2: 2003 but the acceleration was bigger 0,5% than the gravitation. The adding of BJ 37 IWF 350 mm x 175 mm could enhance the vibration frequency from 7,078142-7,3351 Hz as many as 3,630% and the acceleration from 0,001005-0,0009177 m/s2 as many as 8,6865%.Key words: Beam, Plate, Vibration, Frequency, Acceleration.